1970
DOI: 10.3329/bjas.v37i1.9866
|View full text |Cite
|
Sign up to set email alerts
|

Productive And Reproductive Performance Of Indigenous And Crossbred Cattle In Comilla District

Abstract: This study was conducted to compare the productive and reproductive performance of indigenous and crossbred cow likely Friesian, Sahiwal and Sindhi cross. A total of 180 dairy cows were selected randomly from four upazilas of Comilla district. It was observed that mean milk yield and lactation length of indigenous, Friesian cross, Sahiwal cross and Sindhi cross were 2.35±0.04, 7.36±0.11, 4.78±0.08 and 4.03±0.05 litre/day and 218.22±8.35, 284.69±1.64, 251.77±3.66 and 259.77±4.91 days respectively. It reveals th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The variations in DMY possibly incur with genotype, hormonal influences, feeding system, quality and quantity of the feed, irresponsible care taker, ambient temperature and humidity. The average lactation length for HF50%×L50%, HF62.5%×L37.5%, HF75%×L25%, >HF75%×L<25% were 8.54±0.33, 9.40±0.37, 9.08±0.24 and 9.67±0.39 months, respectively and is comparable with the findings of Hasan (1995) and Uddin et al (2008) who reported the average LL varied from 256.3±24.37 to 284.69±1.64 days in Holstein-Local crossbred cattle of Bangladesh. In contrast, Alam et al (2008) found a bit lower LL (217.9 ± 18.7 days) than this study in HF×L crossbred cattle.…”
Section: Discussionsupporting
confidence: 87%
“…The variations in DMY possibly incur with genotype, hormonal influences, feeding system, quality and quantity of the feed, irresponsible care taker, ambient temperature and humidity. The average lactation length for HF50%×L50%, HF62.5%×L37.5%, HF75%×L25%, >HF75%×L<25% were 8.54±0.33, 9.40±0.37, 9.08±0.24 and 9.67±0.39 months, respectively and is comparable with the findings of Hasan (1995) and Uddin et al (2008) who reported the average LL varied from 256.3±24.37 to 284.69±1.64 days in Holstein-Local crossbred cattle of Bangladesh. In contrast, Alam et al (2008) found a bit lower LL (217.9 ± 18.7 days) than this study in HF×L crossbred cattle.…”
Section: Discussionsupporting
confidence: 87%
“…The reported that over all mean value for service per conception was 2.19 in native cows (Zebu cattle) in Bangladesh (Uddin et al, 2008;Mollah et al, 2015), 2.05 ± 1.47 in Holstein Friesian dairy cows in Ethiopia (Consentini et al, 2021) and 2.13 ± 0.037 in local (Sahiwal or Red Sindhi cross) dairy cows (Uddin et al, 2008;Mollah et al, 2015) in rural areas of Bangladesh. Therefore, it can be said that this study's results were less impressive than others.…”
Section: Calving Interval (Ci)mentioning
confidence: 99%
“…The overall mean of this crossbred genotype was 3.96 lit./day/cow. 2017) for L-F crossbred at Manikgonj district of Bangladesh (Khoda et al, 2015;Uddin et al, 2008;Miazi et al, 2007;Rokonuzzaman et al, 2009;Islam et al, 2016;Alam et al, 2008;Mondal et al, 2005;Nahar, 2007;Ratan et al, 2017). The daily milk yield variation possibly occurred due to biological phenomenon, hormonal influences, feeding system, quality and quantity of feed, irresponsible care taker, number of observation and severe intensive sun light.…”
Section: Milk Yield Of 50% Local-50% Friesian Crossbred Cowsmentioning
confidence: 99%